2013 IEEE Radio Frequency Integrated Circuits Symposium (RFIC) 2013
DOI: 10.1109/rfic.2013.6569600
|View full text |Cite
|
Sign up to set email alerts
|

A WLAN RF CMOS PA with adaptive power cells

Abstract: A CMOS linear PA for IEEE 802.11 b/g applications is implemented in a 0.13 μm process including all matching networks. An adaptive power cell (APC) scheme is proposed to achieve high linear output power and efficiency and applied to the PA, which delivers the output power of 20.5 (19.5) dBm with the PAE of 20.2(17.5)% for an 802.11g modulated signal with the EVMs at -25(-28) dB. Index Terms -AM to AM, AM to PM, CMOS Power Amplifier (PA), adaptive, error vector magnitude (EVM), linearization, IMD3, WLAN, 802.11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…With proposed CG bias circuit, PA shows 1 dB improvement in linear output power at 235 dBc IMD 3 with 2-tone simulation. In measurement, it improves 0.7 dB in linear output power at 228 dB EVM in comparison to previous work [2]. Therefore, it is shown that the CMOS PA is stabilized and linearized with the proposed CG bias network.…”
Section: Design Of Cg Bias Circuit With Reduced Sensitivitymentioning
confidence: 61%
“…With proposed CG bias circuit, PA shows 1 dB improvement in linear output power at 235 dBc IMD 3 with 2-tone simulation. In measurement, it improves 0.7 dB in linear output power at 228 dB EVM in comparison to previous work [2]. Therefore, it is shown that the CMOS PA is stabilized and linearized with the proposed CG bias network.…”
Section: Design Of Cg Bias Circuit With Reduced Sensitivitymentioning
confidence: 61%
“…The proposed quasi-DPA has a folded CT in the output matching network, and this provides several advantages, namely, reduced insertion loss, small size, and wideband characteristics. In addition, the quasi-DPA uses the adaptive power cell (APC) technique, which was already studied regarding the linearity of the main amplifier [14]. An adaptive bias circuit (ADB) [15] was designed for the auxiliary amplifier, and it is biased in class-C.…”
Section: Design Of a Quasi-doherty Pa With An Adaptive Power DIVmentioning
confidence: 99%
“…The major nonlinear characteristics of CMOS PAs are due to capacitance variations. Therefore, there have been many efforts to reduce the capacitance variations of CMOS power transistors . These can be categorized into two methods.…”
Section: Introductionmentioning
confidence: 99%
“…In the first approach, capacitance variations of NMOS's are compensated by those of PMOS's . In the other approach, the capacitances of CMOS transistors are averaged at various biases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation